Literature analysis on asparagus roots and review of its functional characterizations - Guo, Yaodong; Liu, Zhe; Wan, Yingjie; Zhang, Yanyan; Abdu, Hassan Idris; Yang, Meng; Pei, Jinjin; Yue, Tianli; Zhang, Xianbin; Hacimuftuoglu, Ahmet; Abd El-Aty, A. M. (Frontiers in Nutrition, 2023)
Asparagus root (AR) is utilized as a traditional herbal medicine globally because it contains various bioactive compounds, such as polyphenols, flavonoids, saponins, and minerals. The composition profiles of AR are strongly affected by its botanical and geographical origins. Although minerals and heavy metals are minor constituents of AR, they play a crucial role in determining its quality and efficacy. Herein, a comprehensive classification of AR, its phytochemistry, and pharmacology were reviewed and interpreted. Potentially eligible articles (in English) were identified through an electronic search of the Web of Science database (2010–2022) and Google. We used the primary search term “Asparagus roots” combined with the words “pharmacology,” “bioactive compounds,” “physicochemical properties,” “health benefits” to find the relevant literature. We screened titles, keywords, and abstracts of the publications obtained from the database. If deemed appropriate, a full copy of the article was obtained for further assessment. Different asparagus species might have the potential for use as herbal medicine and functional food. The phytochemical studies revealed the presence of various bioactive compounds as valuable secondary metabolites. The dominant class of bioactive compounds in AR is flavonoids. Further, AR displayed significant pharmacological effects, such as antioxidant, antimicrobial, antiviral, anticancer, anti-inflammatory, and antidiabetic effects, as shown in animal and human studies. This review provides a valuable resource to enable a thorough assessment of the profile of Asparagus root as a functional ingredient for pharmaceutical and food industries. In addition, it is anticipated that this review would provide information to health care professionals seeking alternative sources of critical bioactive compounds.